Straw mulch and irrigation effect on wheat under various crop establishment techniques in Brahmaputra Valley of Assam, India - SAIKIA, T.P.; BORDOLOI, P.K.; KALITA, BINOD; BORAH, NILAY (Journal of Soil and Water Conservation, 2022)
An experiment was carried out in the Brahmaputra valley of Assam, India to assess the performances of wheat (Triticum aestivum L.) under various crop establishment techniques and to find out the influence of mulching and irrigation on productivity and profitability of wheat cultivation. Results indicated the superiority of Conventional tillage (CT) in terms of grain yield over zero tillage (ZT) and Bed planting (BP). Significantly higher grain yield was recorded under Conventional tillage (CT) over that under Zero tillage (ZT) and Bed planting (BP). Grain yield pooled over three years indicated increase of 21.5 and 7.6 % under CT over that under ZT and BP, respectively. Grain yield increased significantly under mulch treated plots over that under non-mulched plots, irrespective of irrigation levels. The maximum benefit-cost (B: C) ratio (2.51) was recorded with mulching and three irrigations. It was revealed that conventional tillage along with paddy straw mulching @ 4 t/ha and three irrigations is a good option for the wheat farmers of the Assam in terms of productivity and profitability.